Dakwah Humanis Pendekatan Sosiologis-Antropologis - Bukhari, Bukhari (Universitas Islam Negeri Imam Bonjol Padang, 2012)
The idea is basically humanist Islamic preaching, so it must be held within the framework of human interest. Islamic preaching is the process of humanization, human pemanusiaan process. Humanization core awareness is a process-oriented to optimization potential and human values that exist in human beings. Therefore it is necessary that the dynamic preaching. The humanist Islamic preaching -oriented identity formation humane man with peace, wisdom, wisdom and justice. Islamic preaching humanistic approach emphasizes the importance of persuasion with respect to the humanitarian aspects of psychological, sociological, anthropological, cultural and educational in preaching. The humanist Islamic preaching is to educate, enlighten, educate and awaken people as manuasia noble, superior, respectable and dignified.